Drug safety evaluation of sorafenib for treatment of solid tumors: consequences for the risk assessment and management of cancer patients. (May 2014) - Huillard, Olivier; Boissier, Emilie; Blanchet, Benoit; Thomas-Schoemann, Audrey; Cessot, Anatole; Boudou-Rouquette, Pascaline; Durand, Jean-Philippe; Coriat, Romain; Giroux, Julie; Alexandre, Jerome; Vidal, Michel; Goldwasser, Francois
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Sorafenib&logicalOpe1=OR&field2=articletitle&text2=Sorafenib&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Sorafenib is a multi-tyrosine kinase inhibitor (TKI). Considerable clinical experience has been accumulated since its first Phase III clinical trial in metastatic renal cancer patients in 2007. The management of its early acute toxicity in fit patients is well known. The management of prolonged treatment becomes the new challenge. Areas covered: Using sorafenib as a key word for PubMed search, we review preclinical and clinical data and discuss the pharmacokinetics and pharmacodynamics of sorafenib, its acute and cumulative toxicities and their consequences for patient management. Expert opinion: The systematic multi-disciplinary risk assessment of cancer patients prior to TKI initiation reduces the risks of acute and late toxicity, especially drug–drug interactions and arterial risks. Sarcopenia is now identified as a major risk of severe toxicity. The very diverse clinical pictures of cumulative toxicity must be known. The monitoring of sorafenib systemic exposure is helpful especially in elderly patients. Moreover, at disease progression, it allows distinguishing between underexposure to sorafenib and truly acquired resistance to the drug. The optimal use of sorafenib should allow improving the reported results of flat-dose. Finally, most of this knowledge could be used for the development and optimal use of the other TKIs.